2007
DOI: 10.1091/mbc.e07-05-0503
|View full text |Cite
|
Sign up to set email alerts
|

Kalirin/Trio Rho Guanine Nucleotide Exchange Factors Regulate a Novel Step in Secretory Granule Maturation

Abstract: The molecular mechanisms involved in the maturation of secretory granules, organelles that store hormones and neuropeptides, are poorly understood. As granule content proteins are processed, the composition of granule membranes changes, yielding constitutive-like secretion of immature content proteins and producing secretagogue-responsive mature granules. Constitutive-like secretion was not previously recognized as a process subject to regulation. We show that Kalirin and Trio, homologous Rho guanine nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 86 publications
1
45
0
Order By: Relevance
“…secretion (Ferraro et al, 2007), whereas intersectin 1L, a GEF for Cdc42 activates the exocytotic machinery in PC12 cells (Malacombe et al, 2006). Additionally, βPix, an exchange factor for Rac1 has been described to be recruited by Scrib at the plasma membrane during exocytosis (Audebert et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…secretion (Ferraro et al, 2007), whereas intersectin 1L, a GEF for Cdc42 activates the exocytotic machinery in PC12 cells (Malacombe et al, 2006). Additionally, βPix, an exchange factor for Rac1 has been described to be recruited by Scrib at the plasma membrane during exocytosis (Audebert et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Kalirin was originally identified through its association with peptidylglycineamidating monooxygenase (PAM), a neuropeptide processing enzyme that functions in DCVs (Alam et al 1997;Mains et al 1999). Kalirin and Trio modulate DCV maturation in pituitary derived AtT-20 neuroendocrine cells and their isoforms are differentially associated with Golgi, immature DCVs, and endosomes (Ferraro et al 2007). Increasing Kalirin or Trio activity depletes immature DCVs of their hormone cargo, while Kalirin or Trio inhibition increases the amount of mature hormone product in mature DCVs.…”
Section: Unc-73 Rhogef-2 Isoforms and Neuromodulatory Protein Signalingmentioning
confidence: 99%
“…It might be another example of a value of differentiated secretion of progastrin-processing products. It was recently shown that the Rho homologous guanine exchange factors, Kalirin and Trio, can modulate secretion response of the constitutive-like vesicles and the mature granules (39). Thus, secretion of glycine-extended gastrins over gastrins might be subjected to specific regulation.…”
Section: N-terminal Processing Begins In the Earlymentioning
confidence: 99%